Konsep Salam dan Relevansinya dalam Interaksi Sosial:Studi QS An-Nisa: 86 pada Tafsir Al-Furqan - Al khanafi, Muhammad Imam Sanusi; Aziz, Thoriqul; Ihsani, A. Fikri Amiruddin (Jawa Timur: Prodi. Ilmu Al Quran dan Tafsir Fakultas Ushuluddin IAI Tarbiyatut Tholabah, 2025)
Studies on ethical principles in contemporary Qur’anic exegesis hold significant potential for advancing contextual and socially relevant interpretations of the Qur’an. This research provides an in-depth analysis of Ahmad Hassan’s Tafsir Al-Furqan, focusing on the construction of the concept of salam (greeting of peace) and its implications for social ethics in contemporary Muslim communities. The primary aim of this study is to explore how salam is articulated not merely as a ritualized greeting but as an ethical principle emphasizing peace, moderation, and social responsibility. The study employs a qualitative-descriptive approach with thematic-conceptual analysis, examining Qur’anic verses related to salam, documenting Ahmad Hassan’s exegetical interpretations, and situating them within modern socio-religious contexts. Primary data were derived from Tafsir Al-Furqan, supported by secondary sources from global Qur’anic studies, Islamic ethics literature, and social research. Findings indicate that salam in Tafsir Al-Furqan functions as a moral instrument that fosters trust, social solidarity, and harmonious interactions, effectively linking Qur’anic principles with contemporary social practices. The main contribution of this study lies in presenting an exegetical framework that integrates Qur’anic moral guidance with modern social realities, thereby extending the horizon of Qur’anic interpretation toward a more interdisciplinary, dialogical, and socially transformative discourse.